2018
DOI: 10.3390/app8091677
|View full text |Cite
|
Sign up to set email alerts
|

Fault Detection of Stator Inter-Turn Short-Circuit in PMSM on Stator Current and Vibration Signal

Abstract: The stator inter-turn short circuit fault is one of the most common and key faults in permanent magnet synchronous motor (PMSM). This paper introduces a time–frequency method for inter-turn fault detection in stator winding of PMSM using improved wavelet packet transform. Both stator current signal and vibration signal are used for the detection of short circuit faults. Two different experimental data from a three-phase PMSM were processed and analyzed by this time–frequency method in LabVIEW. The feasibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…(2) Vibration When the motor is running normally, the stator vibration frequency should be twice the frequency of the power supply. But inter-turn short-circuit fault and three-phase asymmetry of the motor windings will cause magnetic field asymmetry, resulting in abnormal vibration, which will produce the harmonic components of 4 f s and 8 f s in addition to the fundamental frequency of 2 f s in the vibration [64].…”
Section: Frequency Domain Methodsmentioning
confidence: 99%
“…(2) Vibration When the motor is running normally, the stator vibration frequency should be twice the frequency of the power supply. But inter-turn short-circuit fault and three-phase asymmetry of the motor windings will cause magnetic field asymmetry, resulting in abnormal vibration, which will produce the harmonic components of 4 f s and 8 f s in addition to the fundamental frequency of 2 f s in the vibration [64].…”
Section: Frequency Domain Methodsmentioning
confidence: 99%
“…Permanent magnet synchronous motors (PMSMs) have been widely used in automotive traction drives due to their high performance, efficiency, and power density [1][2][3]. PMSMs should be operated within a specified range of temperature rise without any risk of demagnetization and stator winding failure [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…PMSM faults are classified in three groups as mechanical faults, magnetic faults and electrical faults [10]. Statistics indicate that more than 47 % of the electrical motor faults are due to electrical faults [11].…”
mentioning
confidence: 99%
“…Current studies indicate stator winding faults among the most frequently observed faults in electrical machines including PMSMs. Stator fault is due to the gradual decrease in the insulation between the stator winding threads [10,[12][13][14]. The fault detection is the process of detecting and identifying the type and scope of the fault.…”
mentioning
confidence: 99%
See 1 more Smart Citation